Agricultural Land Protection by Spatial Planning in Bulgaria - Moteva, Milena; Marinova, Bisserka (Geomatics and Environmental Engineering, 2020)
Agricultural land is a basic resource for the livelihood of the Bulgarian population. However, its management is unstable and is connected with many unresolved or wrongly resolved problems which make it difficult to exercise its underlying function. This is mainly due to fragmented land legislation that has a number of disadvantages: the transformation of agricultural land into urban land is easy, control of land quality is poor, and there is a deficiency of agricultural spatial planning regulations. One of the specific tools for preserving the natural function of agricultural land is spatial planning, subject to the strategic documents of the country. According to a newly elaborated concept on agricultural territory planning, this process is two‑staged: on the municipal and on‑farm level. The objectives of the paper are: 1) to analyze the effectiveness of national legislation in regard to preserving the natural function of agricultural land; 2) to defend the necessity of the normative framework completion with precise spatial planning rules for agricultural land, and finally; 3) to draw attention to a new concept on agricultural territory planning by presenting the basic cadastral and specific data for performing spatial GIS analyses and elaborating spatial plans. Data from national statistical institutions were used, and methods of analysis and synthesis were applied. The data needed for GIS analyses and elaboration spatial plans for agricultural territory are listed. The paper asserts that spatial planning is a tool for regulating agricultural land use, for setting territory conditions for preserving and improving land quality, for protecting land tenure rights and for developing successful and high‑income agribusiness.